Controlling the Substitution Pattern of Hexasubstituted Naphthalenes by Aryne/Siloxyfuran Diels–Alder Additions: Regio‐ and Stereocontrolled Synthesis of Arizonin C1 Analogs. Issue 20 (29th May 2017) - Neumeyer, Markus; Kopp, Julia; Brückner, Reinhard
Abstract : 3, 4‐Dimethoxybenz‐1‐yne and 2‐siloxylated furans without or with a bromine atom at C‐3 undergo Diels–Alder reactions with orientational selectivity. Hydrolysis furnished a bromine‐free or a bromine‐containing naphthalene, respectively. Bromination of the former provided a regioisomer of the latter. Either of the two compounds was processed to give a variety of unnatural naphthoquinonopyrano‐γ‐lactones. This occurred by a succession of (1) Heck coupling, (2) asymmetric dihydroxylation, (3) oxa‐Pictet–Spengler cyclization, and (4) oxidation. The fifteen monomeric naphthoquinonopyrano‐γ‐lactone structures that we prepared resemble the natural product (–)‐arizonin C1 or its C‐5 epimer. Accordingly, they represent hexasubstituted naphthalenes likewise. The sixteenth naphthoquinonopyrano‐γ‐lactone that we synthesized is a kind of dimer. Its moieties are bridged differently than those in naturally occurring naphthoquinonopyrano‐γ‐lactone dimers. Abstract : 3, 4‐Dimethoxybenz‐1‐yne and 2‐siloxylated furans with or without 3‐bromine underwent Diels–Alder reactions with orientational selectivity. Hydrolysis gave a Br‐containing or a Br‐free naphthalene, respectively. Bromination of the latter provided a regioisomer of the former. In four steps, these compounds delivered unnatural naphthoquinonopyrano‐γ‐lactones; they resemble the natural product (–)‐arizonin C1.